Assessing the Knowledge Regarding Biomedical Waste Management Practices in a Multi-Speciality Hospital - Pathak, Ketaki N.; Pathak, Niranjan P.; Kulkarni, Anjali V. (Medicine and Medical Research: New Perspectives Vol. 7, 2024)
Aims: The present study assesses the knowledge of Biomedical waste (BMW) categories, colour coding, transport, storage, and disposal of Biomedical waste among healthcare workers. Background: Hospital waste (Biomedical waste) is dangerous due to its hazardous and infectious nature in comparison to other kinds of waste. Almost 75-90% of the waste produced by hospitals, nursing homes, etc. is non-risk in nature as it is generated from administrative and general housekeeping. Materials and methods: This cross-sectional study was conducted over the duration of 1 month, in the Multi-speciality Hospital, Pune, India. A predesigned questionnaire with closed-ended questions was used to conduct this study on HCWs. Data related to awareness and knowledge about various aspects of biomedical waste management were collected. Results: Out of 100 HCWs, 40 doctors knew all BMW categories. 45 doctors and 40 nursing staff (a total of 85 HCWs) correctly answered questions on colour coding. Only 30 doctors and 21 nursing staff knew about BMW transport. 25 doctors and 18 nurses answered correctly about BMW storage and disposal. In our study, 60% of healthcare workers including doctors and nursing staff were aware of BMW categories. 85% of healthcare workers had knowledge about colour coding of biomedical waste. Conclusion: Vigorous and repeated training and evaluation are needed to bridge the knowledge gaps among HCWs. Hands-on sessions on various aspects of BMW management under supervision need to be organised separately involving each category of HCWs as well as for the frontline staff (Pharmacists, billing, reception) in every healthcare organization to improve compliance amongst all stakeholders.